Efektifitas ASEAN Socio Cultural Community dalam Menanggulangi Polusi Asap Lintas Batas (Studi Kasus Indonesia) - Musfiroh Musfiroh (An Nafi': Multidisciplinary Science, 2024)
The ASEAN Socio-Cultural Community has its main driving elements, one of which is environmental issues. In response to this issue, ASEAN member countries signed the ASEAN Agreement on Transboundary Haze Pollution (AATHP) on June 10 2002, and it officially came into effect in 2013. AATHP is an international agreement between ASEAN countries that focuses on the environment. Indonesia itself only ratified this agreement in 2014, but the AATHP is still not implemented properly due to differences in domestic regulations with the regulations set by the AATHP. The results of this research found that however, looking at the example of the AATHP agreement that has been explained, it can be seen that this AATHP agreement is seen as not having a significant impact. This occurs due to a lack of awareness of the importance of implementing AATHP in each country, low compliance with regulations and awareness of the parties responsible for forest and land fires, in this case Indonesia which is one of the sources of forest fires. environment and public health.